Fixing Device for a Planar Object by Incorporating Jamming Transition Phenomenon and a Suction Unit - Akira Bekku; Yoshikazu Nakajima (Journal of Robotics)
This paper presents a versatile method to install a small machining robot onto a planar or slightly curved object. Normally, gripping tools provide a rigid connection between a robot and a target. However, if there is no graspable area on the target, the gripper cannot perform well. To overcome this problem, we proposed a deformable device that works as a universal suction pad and that can hold an ungraspable target by utilizing the jamming transition phenomenon. We determined the effect of the type of grains on the jamming transition phenomenon in terms of stability under jammed conditions. By comparing the four types of grains, we found that the tetrahedral-shaped grains performed the best. Subsequently, we evaluated the performance of the device. The suction force was 166-N when the proposed device was affixed to a curved target. Next, we evaluated the stiffness of the device. The average deformations of the device were 0.10 mm, 0.35 mm, and 0.04 mm, respectively, when 50-N downward vertical, horizontal, and upward vertical directional loads were applied to the device, which was affixed to the curved target. The results suggest that the proposed device performed well in affixing a robot onto a target.